2023
DOI: 10.1111/ppl.13961
|View full text |Cite
|
Sign up to set email alerts
|

High potential for foliar water uptake in early stages of leaf development of three woody angiosperms

Abstract: Foliar water uptake (FWU) is a widespread mechanism that may help plants cope with drought stress in a wide range of ecosystems. FWU can be affected by various leaf traits, which change during leaf development. We exposed cut and dehydrated leaves to rainwater and measured FWU, changes in leaf water potential after 19 h of FWU (ΔΨ), minimum leaf conductance (gmin), and leaf wettability (abaxial and adaxial) of leaves of Acer platanoides, Fagus sylvatica, and Sambucus nigra at three developmental stages: unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Studies have shown that FWU improves plant water status [5,[48][49][50][51]. The effect of wetting on plant Ψ Pre is more significant than for Ψ Mid [10,52], and our results confirm this.…”
Section: Response Of Leaf Ecophysiology To Wettingsupporting
confidence: 85%
“…Studies have shown that FWU improves plant water status [5,[48][49][50][51]. The effect of wetting on plant Ψ Pre is more significant than for Ψ Mid [10,52], and our results confirm this.…”
Section: Response Of Leaf Ecophysiology To Wettingsupporting
confidence: 85%
“…It could be seen that the contact angle of the senescent leaves was significantly reduced (Sun et al, 2014). Looking closely at the surface microstructure, the hierarchical structure on the surface of senescent leaves was no longer evident and the distributed wax tubes almost disappeared (Gou and Guo, 2019;Losso et al, 2023). Similarly over time, the green rape leaves shrunk and curled, the contact angle gradually decreased, and finally the wettability gradually transitioned from hydrophobic to hydrophilic (Zhu and Guo, 2016).…”
Section: Growth Agementioning
confidence: 99%